Growth and population structure of perch in relation to diet in a small humic lake, Valkea-Kotinen - Afolabi, Abideen (2011)
Lake Valkea-Kotinen is a long-term ecological monitoring site in the Evo region of southern Finland .The aim of this study was to investigate the growth and population structure of perch (Perca fluviatilis L.) in relation to diet in Valkea-Kotinen in order to provide reference data for a study investigating effects of increased loading of dissolved organic matter to nearby Lake Alinen Mustajärvi. Valkea-Kotinen was predominantly inhabited by small benthivorous perch. The growth relationship between opercular bone and total length of perch in the lake is similar to those earlier analysed for nearby lakes. Compared to wider growth rates, the growth of perch was slow and similar to those in similar lakes. Analyses of stable carbon and nitrogen isotopes and stomach content revealed that perch were mostly feeding on mayfly nymphs and did not undergo any clear ontogenetic dietary shifts. In summer and autumn, the perch population had more diverse diets than in spring. Zooplankton only contributes to the diet of <100 mm perch in summer, terrestrial insects and small prey fish were almost completely missing from the perch diet. Poor food condition and overall feeding behaviour are suggested to contribute to the observed slow growth and dominance of small individuals in the perch population.